Literature Review: Pengaruh Prenatal Yoga Terhadap Tingkat Kecemasan Ibu Hamil Trimester III - Mayang Damayanti; Sukyati, Ira (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2025)
Background: Pregnant women can experience anxiety because the waiting period for birth is full of uncertainty and fear about events that will occur during the labor process. The level of anxiety in pregnant women can be minimized using non-pharmacological measures, one of which is prenatal yoga. Prenatal yoga is a sport intended for pregnant women, which is useful for reducing anxiety. Objective: To determine the effect of prenatal yoga on the level of anxiety in pregnant women in the third trimester. Method: The research method used is a literature review with secondary data from previous studies, the search is adjusted to keywords and inclusion criteria, and uses the Google Scholar database. Results: Based on 10 articles reviewed, it was found that prenatal yoga has an effect on the level of anxiety in pregnant women in the third trimester. Conclusion: Nurses can apply prenatal yoga to reduce the level of anxiety experienced by pregnant women in the third trimester. Keywords: Pregnant women in the third trimester, prenatal yoga, anxiety level